2022
DOI: 10.30656/ka.v4i1.3328
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Video Edukasi: Upaya Meningkatkan Kesadaran Masyarakat Dalam Mematuhi Protokol Kesehatan Di Era New Normal

Abstract: Early in 2020, we are welcomed by the Corona Virus Disease 2019 (Covid-19) outbreak. The lack of public awareness to always comply with health protocols is one of the triggers of the increasing number of Covid-19 spread in Indonesia. The lack of parental awareness of the importance of disciplining their children to always comply with health protocol regulations, such as not wearing a mask, not keeping distance, and awareness to wash their hands is one of the causes of the spread of covid-19. Therefore, efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, it is found that there are several facts about the current condition while applying this face-to-face learning system. They are a lack of public awareness about the importance of dealing with health protocols, such as, not wearing masks, not keeping a distance and awareness washing hands, as the causes of the spread of COVID-19 (Komarudin & Puspita, 2022). This condition is also found in schools where students still take off their masks and do not wash their hands during the learning process or play with other people.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that there are several facts about the current condition while applying this face-to-face learning system. They are a lack of public awareness about the importance of dealing with health protocols, such as, not wearing masks, not keeping a distance and awareness washing hands, as the causes of the spread of COVID-19 (Komarudin & Puspita, 2022). This condition is also found in schools where students still take off their masks and do not wash their hands during the learning process or play with other people.…”
Section: Introductionmentioning
confidence: 99%